2016
DOI: 10.3389/fmicb.2016.01825
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Transcriptomic Evidence for Carbohydrate Consumption among Microorganisms in a Cold Seep Brine Pool

Abstract: The detailed lifestyle of microorganisms in deep-sea brine environments remains largely unexplored. Using a carefully calibrated genome binning approach, we reconstructed partial to nearly-complete genomes of 51 microorganisms in biofilms from the Thuwal cold seep brine pool of the Red Sea. The recovered metagenome-assembled genomes (MAGs) belong to six different phyla: Actinobacteria, Proteobacteria, Candidatus Cloacimonetes, Candidatus Marinimicrobia, Bathyarchaeota, and Thaumarchaeota. By comparison with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…Sulfate or sulfite was previously reported as the important environmental factors to shape the distribution of bathyarchaeotal subgroups [18,30,57], and genomic evidence for dissimilatory sulfate and sulfite reduction via genes sat-aprAB (sulfate adenylyltransferaseadenylylsulfate reductase) were also reported [17,58]. They both suggested that Bathyarchaeota could participate the global sulfur cycle.…”
Section: Sulfur Metabolismmentioning
confidence: 93%
“…Sulfate or sulfite was previously reported as the important environmental factors to shape the distribution of bathyarchaeotal subgroups [18,30,57], and genomic evidence for dissimilatory sulfate and sulfite reduction via genes sat-aprAB (sulfate adenylyltransferaseadenylylsulfate reductase) were also reported [17,58]. They both suggested that Bathyarchaeota could participate the global sulfur cycle.…”
Section: Sulfur Metabolismmentioning
confidence: 93%
“…More-recent work has shown that members of this phylum can use a broad diversity of alternative electron acceptors in the ocean and likely play a central role in shaping biogeochemical cycles along environmental gradients ( 20 ). Moreover, other studies have shown that Marinimicrobia are present and active in a broad array of marine environments, including coastal and pelagic surface waters, cold seep brine pools, coastal “dead zones,” and oxygen minimum zones (OMZs), and likely mediate key transformations of nitrogen and sulfur throughout the global ocean ( 21 27 ). In contrast to the broad environmental distributions typical of other bacterial phyla, Marinimicrobia are unusual in that the vast majority of known diversity in this group has been observed in marine environments, thereby providing a unique opportunity for comparative genomic analyses to assess the factors shaping their genome evolution throughout their radiation into the contemporary ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Metatranscriptomic analysis was performed using the method described in a previous study (Zhang et al 2016). The quality of the cDNA sequences was controlled using the next-generation sequencing QC toolkit (Patel and Jain 2012) before being assembled by SPAdes Genome Assembler 3.6.1 (Bankevich et al 2012) on a local server.…”
Section: Metatranscriptomic Analysismentioning
confidence: 99%